The Land Rights Which Can Be Given On The Land Management System - Carrissa Shannon Lie; Yohanes Kristian Pranata (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
This research to understand management Right which defined in the Government Regulation No. 18 of 2021 Article 1 No. 3 as the State’s ownership right in which a part of the authorization is given to the Management Right holder. The type of research was juridical normative law research, which was a research that emphasizes in written documents as the main law resources, such as regulations, court decisions, law theories, and scholar’s opinions. There were 2 (two) approaches used to support this research. The first one was statute approach, which was done by analyzing all the related regulations and others that were related to currently law issues. One of the authorities that the holder has is to hand in parts of the Management Right land to a third party and/or cooperating with a third party. If the land is used by a third party, then a Land Right has to be given on the land for the third party’s basis to utilize and/or use the land. The handing of Land Rights to a third party must be done with the holder’s agreement. Therefore, the third party uses the land with the right on a certain land that is initiated on the Management Right land. The main issue that will be discussed is what types of land rights that can be given on the lands. This research is a law research with a normative law research method. Besides that, this research uses statute approach and conceptual approach. The conclusion is the land rights that can be given on the land are Building Rights on Land and Land Use Rights.